2013
DOI: 10.1111/eos.12109
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification with alumina blasting and H2SO4HCl etching for bonding two resin‐composite veneers to titanium

Abstract: The purpose of this study was to investigate the effect of an experimental surface treatment with alumina blasting and acid etching on the bond strengths between each of two resin composites and commercially pure titanium. The titanium surface was blasted with alumina and then etched with 45wt% H2SO4 and 15wt% HCl (H2SO4-HCl). A light- and heat-curing resin composite (Estenia) and a light-curing resin composite (Ceramage) were used with adjunctive metal primers. Veneered specimens were subjected to thermal cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Bond strength was higher for the photo/heat-polymerized (EST) gingiva-colored indirect resin composite than for the light-polymerized (CER) gingiva-colored indirect resin composite in all groups. These results are consistent with those of previous studies of bonding between indirect resin composites and metal alloys, which found photo/heatpolymerized indirect resin composites provided higher bond strengths than did light-polymerized indirect resin composites 25,26) , perhaps due to differences in the size of filler particles, the type of polymerization, and the mechanical properties of gingiva-colored indirect resin composites. Magne et al 27) reported that microtensile bond strengths between resin composites and resinluting material were affected by improved mechanical properties caused by heat treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Bond strength was higher for the photo/heat-polymerized (EST) gingiva-colored indirect resin composite than for the light-polymerized (CER) gingiva-colored indirect resin composite in all groups. These results are consistent with those of previous studies of bonding between indirect resin composites and metal alloys, which found photo/heatpolymerized indirect resin composites provided higher bond strengths than did light-polymerized indirect resin composites 25,26) , perhaps due to differences in the size of filler particles, the type of polymerization, and the mechanical properties of gingiva-colored indirect resin composites. Magne et al 27) reported that microtensile bond strengths between resin composites and resinluting material were affected by improved mechanical properties caused by heat treatment.…”
Section: Discussionsupporting
confidence: 92%
“…That could indicate formation of solid compounds of Ti and P, such as titanium phosphide, TiP, or titanium phosphate, Ti 3 (PO 3 ) 4 . At 60°C in the TiCl 3 ‐H 3 PO 4 system a formation of layered titanium (IV) hydroxophosphate, Ti (OH) 2 (HPO 4 )·H 2 O, and crystalline Ti (HPO 4 ) 2 ·H 2 O has been observed 25 . In silica‐coated surface (sample 6) formation of AlPO 4 is also plausible.…”
Section: Discussionmentioning
confidence: 94%
“…A passivating thin film of TiO 2 is immediately formed within nanoseconds on the Ti surface 25 . This is one reason for the constant presence of oxygen observed on the PT surface: The amount of detected oxygen was vast also according to the XPS analysis of polished Ti surface.…”
Section: Discussionmentioning
confidence: 98%
“…The uniform coating of the BG layer could be seen on the Ti substrate after sol dipcoating on the blasted Ti substrate. Blasting has a great ability to produce many micro and nano-scale cavities on the Ti surface, which are directly related to the induced bond strength 30) . The FE-SEM image obtained for the blasted Ti substrate showed that the rough blasted Ti surface was fully covered after BG coating.…”
Section: Morphology Phase and Elemental Analysismentioning
confidence: 99%